MCP-1/CCR2 interactions direct migration of peripheral B and T lymphocytes to the thymus during acute infectious/inflammatory processes - Hodge, Deborah L. (2012)
Mature lymphocyte immigration into the thymus has been documented in mouse, rat, and pig models, and highly increases when cells acquire an activated phenotype. Entrance of peripheral B and T cells into the thymus has been described in healthy and pathological situations. However, it has not been proposed that leukocyte recirculation to the thymus could be a common feature occurring during the early phase of a Th1 inflammatory/infectious process when a large number of peripheral cells acquire an activated phenotype and the cellularity of the thymus is seriously compromised. The data we present here demonstrate that in well-established Th1 models triggered by different types of immunogens, for example, LPS treatment (a bacterial product), Candida albicans infection (a fungus), and after Trypanosoma cruzi infection (a parasite), a large number of mature peripheral B and T cells enter the thymus. This effect is dependent on, but not exclusive of, the available space in the thymus. Our data also demonstrate that MCP-1/CCR2 (where MCP-1 is monocyte chemoattractant protein-1) interaction is responsible for the infiltration of peripheral cells to the thymus in these Th1-inflammatory/infectious situations. Finally, systemic expression of IL-12 and IL-18 produced during the inflammatory process is ultimately responsible for these migratory events.